Dopamine sudden depletion as a model for mixed depression - Strejilevich, Sergio (2012)
Up to date research on Bipolar Disorders' phenomenology is in keeping with early descriptions made by E. Kraëpelin regarding the overlap in clinical presentation of both manic and depressive symptoms, namely, mixed states. The latter constitute a highly prevalent and characteristic clinical presentation of Bipolar Disorders' and entail therapeutic difficulties, prognostic implications and increased suicidal risk. Notwithstanding, mixed states', more specifically mixed depression, have been underestimated and bypassed to the point where currently neither diagnostic criteria nor specific therapeutic recommendations are provided. In addition to the lack of agreement on nosography and diagnostic criteria, mixed depression is usually excluded from Bipolar Disorders' neurobiological models. Furthermore, renewed interest in the role of dopamine in Bipolar Disorders' physiopathology has left aside hypothesis that may account for the aforementioned clinical presentation. Interestingly enough, other syndromes arising from sudden dopamine depletion such as neuroleptic dysphoria or withdrawal syndromes from dopaminergic drugs, bear remarkable clinical similarities with mixed depression. These syndromes have been subject of further research and may thus provide a model for mixed states' physiopathology.Indeed, this article accounts for clinical similarities between mixed depression, neuroleptic induced dysphoria, and other behavioural syndromes arising from sudden dopamine depletion. After reviewing neurochemical basis of such syndromes we present, to the best of our knowledge, the first neurobiological hypothesis for mixed depression. Specifically, such hypothesis regards over activation symptoms as auto regulatory attempts to compensate for sudden dopaminergic depletion. This hypothesis provides with a beginning step for the neglected problem of mixed depression, a non-antithetic link between the dopaminergic hypothesis for both manic and depressive symptoms, a plausible explanation regarding inter individual variability to mixed depression susceptibility, and suggests new approaches for the development of novel treatments in which dopamine dysregulation should be targeted.